The role of kidney biopsy in immune checkpoint inhibitor nephrotoxicity - Moss, Emily M.; Perazella, Mark A. (Frontiers in Medicine, 2022)
Immune checkpoint inhibitors, medications that boost host immune response to tumor cells, are now at the forefront of anti-cancer therapy. While efficacious in the treatment of patients with advanced cancer, immune checkpoint inhibitors can lead to serious autoimmune side effects involving any organ in the body. Immune checkpoint inhibitor nephrotoxicity is an increasingly recognized cause of acute kidney injury in patients with cancer. This review discusses the clinical and histopathologic diagnosis of immune checkpoint inhibitor nephrotoxicity, highlighting the need for more reliable non-invasive diagnostic testing. We focus on the controversy surrounding the role of kidney biopsy in diagnosis and management of suspected immune checkpoint inhibitor toxicity with inclination toward pursuing kidney biopsy in certain outlined circumstances. Finally, we briefly discuss treatment of immune checkpoint inhibitor nephrotoxicity and the decision to re-challenge immunotherapy in patients who experience these adverse events.